B.P.R.D. 1948 - Mignola, Mike (Dark Horse Comics, 2013)
Atomic-bred monsters are killing civilians in the Utah desert, prompting Professor Bruttenholm, guardian of the child Hellboy, and Anders, an agent possessed by vampires, to investigate. All signs point to a mysterious, glassy element discovered in the desert as the prigin of these dangerous creatures entering our world.